2018
DOI: 10.3390/ma11050765
|View full text |Cite
|
Sign up to set email alerts
|

Finite Element Analysis of Interaction of Laser Beam with Material in Laser Metal Powder Bed Fusion Process

Abstract: A deep understanding of the laser-material interaction mechanism, characterized by laser absorption, is very important in simulating the laser metal powder bed fusion (PBF) process. This is because the laser absorption of material affects the temperature distribution, which influences the thermal stress development and the final quality of parts. In this paper, a three-dimensional finite element analysis model of heat transfer taking into account the effect of material state and phase changes on laser absorpti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(11 citation statements)
references
References 42 publications
(71 reference statements)
0
11
0
Order By: Relevance
“…Therefore, the availability of a physically adequate and fast mathematical model that allows the performance of numerical modeling will facilitate the development and optimization of technological parameters for the direct laser deposition process. A large number of papers describe the use of various numerical schemes of finite element analysis [ 9 , 10 , 11 ], analytical models [ 12 ], and even statistical models [ 13 ] for modeling thermal and hydrodynamic processes. However, in most of them, the case of cladding the bead on a thick and wide substrate is considered.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, the availability of a physically adequate and fast mathematical model that allows the performance of numerical modeling will facilitate the development and optimization of technological parameters for the direct laser deposition process. A large number of papers describe the use of various numerical schemes of finite element analysis [ 9 , 10 , 11 ], analytical models [ 12 ], and even statistical models [ 13 ] for modeling thermal and hydrodynamic processes. However, in most of them, the case of cladding the bead on a thick and wide substrate is considered.…”
Section: Introductionmentioning
confidence: 99%
“…Hence, fully dense parts can be fabricated within a broad volumetric laser energy density range (i.e., laser scan speeds between 400-1400 mm/s, when a laser power of 500 W was employed). Simulation-based studies dealing with the laser-metal interaction during the LPBF process [44][45][46][47] revealed that the laser mainly irradiates the liquid melt pool and not the powder, except at a very high laser scan speeds. This could mean that the high optical absorption values obtained at room temperature for the surface-modified CuCr1 powder are no longer valid during the actual LPBF process.…”
Section: Lpbf Processing Behavior Part Production and Part Chemicalmentioning
confidence: 99%
“…The absorption behavior of laser radiation from metallic powder materials in the PBF-LB/M process represents a decisive factor for the formation of a dense microstructure of the components. On the one hand, the absorption behavior depends on the exposure parameters and consequently, the duration of laser-material interaction as investigated by Fu et al [20] presented with finite element analysis. On the other hand, the material itself represents a significant influencing factor.…”
Section: Laser Absorption Of Metal Powdersmentioning
confidence: 99%